The Indian scad (Decapterus russelli), (Osteichtyes: Carangidae), a new Indo-Pacific fish invader of the eastern Mediterranean - Golani, Daniel (Scientia Marina, 2006)
The Indian scad, Decapterus russelli, is recorded for the first time from the Mediterranean. The presence of this Indo-Pacific species on the Mediterranean coast of Israel is evidently due to migration from the Red Sea via the Suez Canal. The collection of six specimens in the Mediterranean suggests that this species is well established in the Levant.